Sleep Quality and Subjective Cognitive Decline among Older Adults: The Mediating Role of Anxiety/Depression and Worries - McKenna Sun; Qianqian Zhang; Yifei Han; Jianghong Liu (Journal of Aging Research)
Background. Subjective cognitive decline (SCD) in older individuals has been implicated as a possible precursor to Alzheimer’s disease. Poor sleep quality and anxiety/depressive symptoms have been linked to the progression of SCD, but these associations and older adults’ worries have yet to be fully established in the Chinese older adult population, which is one of the largest in the world. The aim of this study was to explore the relationship between sleep quality, anxiety/depression symptoms, and worries, and SCD prevalence among Chinese community-dwelling older individuals. Methods. A total of 707 adults aged between 60 and 99 from Shanghai, China, completed self-report questionnaires that covered their cognitive and mental well-being, as well as demographic information. Subjective cognitive decline (SCD) was evaluated using the memory/cognition syndromes of the old adult self-report (OASR). Sleep quality, anxiety/depression, and worries were measured from their respective sections of the OASR. Results. The general linear regression models showed that poorer sleep quality was associated with an increased prevalence of anxiety/depression symptoms, worries, and SCD among older adults. As suggested by the mediation analysis, anxiety/depression and worries were significant mediators in the relationship between sleep quality and SCD prevalence, and these two factors also have a serial mediation effect between sleep quality and SCD prevalence. Conclusions. Poorer sleep quality is associated with a higher rate of SCD among older adults, and a higher prevalence of anxiety/depression and worries mediate this relationship, suggesting possible mechanism pathways that lead to SCD. These factors may provide the basis for early, targeted interventions for older adults’ mental health preservation and improved quality of life.